Dependence of the state of metabolism on the time of cessation of sports activities of former athletes - Elikov, A. V.; Korosteleva, M. M.; Khanferyan, R. A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to study the main indicators of metabolism in the blood plasma of former athletes, depending on the time of completion of sports activities.